2019
DOI: 10.1002/ijgo.12793
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of randomized controlled trials of atosiban versus nifedipine for inhibition of preterm labor

Abstract: Background Two tocolytic drugs—atosiban and nifedipine—are currently used for first‐line treatment of preterm labor (PTL). Objective To compare the efficacy and safety of atosiban with nifedipine for PTL treatment. Search strategy In May 2017, we searched PubMed, Scopus, Web of Science, and Cochrane Central Register of Controlled Clinical Trials with search terms including “nifedipine”, “atosiban”, and “preterm labor”. Selection criteria Randomized controlled trials of women with PTL. Data collection and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…1 In our institute, Atosiban is the primary tocolytic agent mainly to give time for steroids administration, especially in the case of very early and early preterm labour, providing no contraindication. In a recent systematic review, Ali et al, 13 showed that there is no significant difference between Atosiban and nifedipine regarding prolongation of pregnancy for 48 hours or more or 7 days of more. However, Atosiban resulted in fewer maternal side-effects than did nifedipine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In our institute, Atosiban is the primary tocolytic agent mainly to give time for steroids administration, especially in the case of very early and early preterm labour, providing no contraindication. In a recent systematic review, Ali et al, 13 showed that there is no significant difference between Atosiban and nifedipine regarding prolongation of pregnancy for 48 hours or more or 7 days of more. However, Atosiban resulted in fewer maternal side-effects than did nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations include; the retrospective nature of the research, the small number of the cases to compare, and the limited information about patients variables (comorbidities, the presence of infection (e.g.Group B Strept) as well as neonatal complications details. [10][11][12][13][14]…”
Section: Discussionmentioning
confidence: 99%
“…Then, 300 µg/min − 1 as loading dose for 3 hours and 100 µg/min − 1 as maintenance dose for 48 hours was administered. Alternatively, nifedipine 20 mg, followed by 10 mg each 20 minutes until 40 mg for 1 hour, was administered [44]. Thus, all women received atosiban or nifedipine for < 24 hours.…”
Section: Participantsmentioning
confidence: 99%
“…Using tocolytics in women as labor-inhibiting agents could postpone delivery by inducing myometrium relaxation [ 11 ]. It has been shown that survival rate increases by 3% for every 24 h of labor delay, which allows for further neonatal rescue intervention and the administration of alternative treatments, such as antenatal corticosteroids, during the extended period until delivery [ 12 , 13 ]. Several tocolytic classes are commonly used, including ritodrine hydrochloride, prostaglandin antagonists indomethacin and ketorolac, the β-adrenoceptor agonist ritodrine, magnesium sulfate, the oxytocin receptor antagonist atosiban, the calcium channel-blocking agent nifedipine, and others.…”
Section: Introductionmentioning
confidence: 99%